Interfrequency Performance Characterizations of GPS During Signal Outages From an Anomaly Crest Location. Issue 6 (7th June 2019) - Biswas, T.; Ghosh, S.; Paul, A.; Sarkar, S.
Abstract: Introduction of new navigation signals L2C (1227.60 MHz) and L5 (1176.45 MHz) to the existing GPS (Global Positioning System) spectrum, under the modernization program of GPS offers the improvement of position accuracy. The present study aims to understand the relative robustness of the L2C and L5 signals compared to legacy L1 C/A signal during periods of scintillations in terms of durations of cycle slips encountered from an anomaly crest location, Calcutta (22.58°N, 88.38°E geographic; magnetic dip 32°N). The data analyzed in this study were recorded during the vernal equinox of 2014 (February–April), a period of high solar activity of cycle 24. Results obtained from the comparative analyses, which are perhaps one of the first from the Indian longitude sector, indicate GPS L5 to be more robust than L1 C/A and L2C in terms of occurrence and duration of cycle slips under adverse ionospheric conditions. Furthermore, loss‐of‐lock events of duration greater than 6 s are found to be more frequent for S 4 ≥ 0.6. It is found that frequency sensitivity of the GPS spectrum, in terms of occurrence of cycle slips and loss of locks are in conformity with earlier results from the equatorial region but are different from the high latitudes with respect to local time of occurrence and geomagnetic activity. Key Points: Relative robustness of the GPS L2C and L5 signals with legacy L1C/A signal in terms of cycle slips Correlation of intensity of amplitude scintillation with duration of cycle slip at L1C/A, L2C, and L5 frequency of GPS Comparative study of loss of lock over three frequencies of GPS above ICAO mentioned standards (6 s) from Calcutta